Extinction of a heterogeneous chain after several reinforcement schedules - D'Andrea, Thomas (1969)
Rats were conditioned to emit the following two-member chain of responses on two different operanda always available: responses on a vertical bar produced a discriminative stimulus for food-reinforced responding on a horizontal bar. Responses on the vertical bar produced a discriminative stimulus on a variable-interval 1-min schedule, and the horizontal bar produced food on a variable ratio of 10 responses. Control conditions were included in which vertical bar responses were also food-reinforced simultaneous with the onset of the discriminative stimulus for the horizontal bar response and a tandem schedule which had the same response requirements but without different exteroceptive stimuli associated with the separate components of the response chain. The latter condition greatly retarded acquisition of the response chain compared to the other schedules studied here and compared to reports in the literature on homogeneous (single operandum) response chains. Intermittent reinforcement of the chain led to greater resistance to extinction of both members and the chain remained intact longer in the sense that stimulus control was maintained.